Characteristics of meteorology and freeze-thaw in high-latitude cold regions: a case study in Da Xing’anling, Northeast China (2022–2023) - Shang, Yunhu; Cao, Yapeng; Li, Guoyu; Gao, Kai; Zhang, Hang; Sheng, Jie; Chen, Dun; Lin, Juncen (Frontiers in Earth Science, 2025)
Meteorological characteristics and freeze-thaw processes are crucial indicators guiding regional economic development and practical production. The Da Xing’anling Mountains, serving as a transitional zone between continuous permafrost and seasonal frozen ground in northeastern China’s high latitudes, understanding the meteorological parameters and freeze-thaw development patterns in this region can significantly enhance the accuracy of permafrost zoning maps and validate climate simulation models. Based on meteorological and ground temperature monitoring data from 2022–2023, this study analyzed the meteorological characteristics and seasonal freeze-thaw processes of Jagdaqi (southern Da Xing’anling Mountains), which is located at the boundary between permafrost and seasonally frozen soil. The results indicate: (1) At a height of 5 m, the annual average temperature is 1.04°C. The air-freezing index and air-thawing index are −2318.95°Cd and 2698.52°Cd, respectively, categorizing it as a severe cold region. (2) The total annual precipitation is 397.1 mm, with summer rainfall accounting for 77.4% and winter rainfall only 11.3%. (3) The prevailing wind direction is from the northwest, accounting for approximately 47% of the total annual wind direction frequency. Annual wind speeds range from 0.045 to 10.33 m/s, with an average speed of 1.51 m/s. (4) At heights of 5 m and 10 m, the annual average relative humidity is 63.49% and 62.1%, respectively, reaching its lowest in May at 44.58% and 43.38%. (5) The study area is located in a seasonal frozen ground region, with maximum frost depths occurring in early to mid-March, ranging between 1.93–1.99 m, classified as middle-thick seasonally frozen ground. These findings hold valuable implications for ecological conservation, resource management, and engineering construction, enhancing the accuracy and applicability of models and permafrost zoning maps in this region.